2017
DOI: 10.1016/j.adro.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Reirradiation with stereotactic body radiation therapy after prior conventional fractionation radiation for locally recurrent pancreatic adenocarcinoma

Abstract: PurposeLocally recurrent pancreatic cancer after prior radiotherapy is a therapeutic challenge with limited treatment options. This study examines the safety and efficacy of stereotactic body radiation therapy (SBRT) for locally recurrent pancreatic adenocarcinoma after prior conventional fractionation radiotherapy (CRT).Methods and materialsOutcomes from all patients treated with SBRT for locally recurrent pancreatic adenocarcinoma after prior CRT at our institution were reviewed. A total of 23 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 28 publications
0
38
3
Order By: Relevance
“…Patients’ clinical stage was not reported in nine studies. 6 , 8 , 11 14 , 16 , 17 In one study, 100% of patients had cT4 tumor stage, 5 while in another trial, this rate was 87.5%. 10 In two studies only, patients with stage II–IV were enrolled 7 , 15 and in another, all patients had T1–3 N0 M0 PC.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients’ clinical stage was not reported in nine studies. 6 , 8 , 11 14 , 16 , 17 In one study, 100% of patients had cT4 tumor stage, 5 while in another trial, this rate was 87.5%. 10 In two studies only, patients with stage II–IV were enrolled 7 , 15 and in another, all patients had T1–3 N0 M0 PC.…”
Section: Resultsmentioning
confidence: 99%
“…From a total of 231 retrieved publications, after applying the selection criteria, 14 studies were found suitable for the analysis ( Figure 1 ). 4 17 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations